Direct and Sensitive Electrochemical Detection of Bisphenol A in Complex Environmental Samples Using a Simple and Convenient Nanochannel-Modified Electrode - Huang, Jie; Zhang, Tongtong; Dong, Guotao; Zhu, Shanshan; Yan, Fei; Liu, Jiyang (Frontiers in Chemistry, 2022)
Rapid, convenient, and sensitive detection of Bisphenol A (BPA) in complex environmental samples without the need for tedious pre-treatment is crucial for assessing potential health risks. Herein, we present an electrochemical sensing platform using a simple nanochannel-modified electrode, which enables the direct and sensitive detection of BPA in complex samples. A vertically ordered mesoporous silica-nanochannel film (VMSF) with high-density nanochannels is rapidly and stably grown on the surface of a electrochemically activated glassy carbon electrode (p-GCE) by using the electrochemically assisted self-assembly (EASA) method. The high antifouling capability of the VMSF/p-GCE sensor is proven by investigating the electrochemical behavior of BPA in the presence of model coexisting interfering molecules including amylum, protein, surfactant, and humic acid. The VMSF/p-GCE sensor can sensitively detect BPA ranged from 50 to 1.0 μM and 1.0–10.0 μM, with low detection limits (15 nM). Owing to the electrocatalytic performance and high potential resolution of p-GCE, the sensor exhibits high selectivity for BPA detection in the presence of common environmental pollutants, including bisphenol S (BPS), catechol (CC), hydroquinone (HQ), and 4-nitrophenol (4-NP). In combination with the good antifouling property of the VMSF, direct detection of BPA in environmental water samples and soil leaching solution (SLS) is also realized without separation pretreatment. The developed VMSF/p-GCE sensor demonstrated advantages of simple structure, high sensitivity, good antifouling performance, and great potential in direct electroanalysis of endocrine-disrupting compounds in complex samples.